2012
DOI: 10.1017/s0031182012000935
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoptic mange and cheetah conservation in Masai Mara (Kenya): epidemiological study in a wildlife/livestock system

Abstract: The sanitary control of threatened wild animals is of pivotal interest for their conservation. This task, however, is highly complex in wildlife/livestock systems. In this paper we report findings from a 2-year cross-sectional study of the epidemiology and attempted control of a Sarcoptes mite infestation in the threatened cheetah population in Masai Mara (Kenya), and discuss its interaction with sympatric wild (lion, wildebeest and Thomson's gazelle) and domestic (dog, cattle and sheep) animals. Sarcoptes sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 36 publications
1
29
1
Order By: Relevance
“…In the case of S. scabiei , affected animals usually need 2-3 doses of drug (such as ivermectin) with a temporal interval of 2-4 weeks, to guarantee efficient treatment. However, this is impracticable with wild animals, due to climatological, territorial and logistical factors, especially with the elusive species [24]. And hence the radio-collars could be of great help, allowing localizing the animals under treatment whenever is necessary for repeated treatment purpose, or just to observe the efficacy and results of the previous treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of S. scabiei , affected animals usually need 2-3 doses of drug (such as ivermectin) with a temporal interval of 2-4 weeks, to guarantee efficient treatment. However, this is impracticable with wild animals, due to climatological, territorial and logistical factors, especially with the elusive species [24]. And hence the radio-collars could be of great help, allowing localizing the animals under treatment whenever is necessary for repeated treatment purpose, or just to observe the efficacy and results of the previous treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It would seem logical that prey-to-predator transfer and coevolution of the parasite in these predator-prey associations are important in the transfer of S. scabiei between hosts and thus the sharing of a common strain of S. scabiei between prey and predator is very likely. Gakuya et al [84, 85] suggested a prey-to-predator transfer between wild felids and ungulates in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…This includes a statement of comprehensive income, referred to as a statement of profit or loss, and often also includes a statement cash flow and a statement of changes in equity. Financial statements reflect the financial effects of business data, transactions and events on the entity [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study conducted a multiple regression analysis so as to determine the regression coefficients (β) which shows that β 0 =1.238 and which means that all the independent variables such as profitability ratios (X 1 ), Liquidity Ratios (X 2 ); Efficiency ratios (X 3 ), Leverage ratios (X 4 ) and Market value ratios (X 5 ) have an a significant contribution in prediction of business sustainability even if the x variable equal to zero means Y=1.238 and the model equation become Y=1.238+ 0.258X 1 +0.367X 2 +0.423X 3 +0.157X 4 +0.345X 5 . Hence, β0=Constant term β (1-5)=represent the model parameters or coefficients; 0.258 as contribution of profitability ratios, .367 as contribution from Liquidity Ratios, .423 contribution of Efficiency ratios, .157 contribution of Leverage ratios and .345 as Market value ratios contribution.…”
Section: Analysis Of Financial Indicators and Sustainability Determinmentioning
confidence: 99%